Case Report: A Rare Case of Coexisting of Autoimmune Polyglandular Syndrome Type 3 and Isolated Gonadotropin-Releasing Hormone Deficiency - Jiang, Qiuhui; Wu, Ting; Zhang, Yuxian; Wang, Shunhua; Wang, Liying; Su, Weijuan; Lin, Mingzhu; Li, Xuejun (Frontiers in Immunology, 2021)
APS is defined as the coexistence of at least two kinds of endocrine autoimmune diseases. APS type 3 comprises autoimmune thyroid diseases and other autoimmune diseases but does not involve autoimmune Addison’s disease. To date, quite a few multifarious combinations were described. However, according to what we know, there is no case report of an APS-3 patient complicated with the autoimmune hypothalamic disease. We recently encountered a 43-year-old woman with a one-year history of Graves’ disease (GD) and a four-month history of type 1 diabetes presented with hyperthyroidism and hyperglycemia. Her menopausal age (42 years old) is earlier than the average person while blood FSH and LH levels were obviously below normal levels comparing with those women in physiological menopausal states. After the GnRH stimulation test, she was diagnosed with secondary amenorrhea attributed to suspected autoimmune Hypothalamitis and APS type 3 associated with Graves’ disease and LADA. This rare case warns us that the hypothalamus cannot be spared from the general autoimmune process. It is essential to carry out the GnRH stimulation test when encountering APS patients who are combined with secondary menopause.